2021
DOI: 10.1108/prr-12-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Faculty perception of teaching translation courses online during Covid-19

Abstract: Purpose The spread of Covid-19 has led to the closure of educational institutions worldwide, forcing academic institutions to find online platforms. The purpose of this paper is to accelerate the development of the online learning (OL) environments within those institutions. The Covid-19 pandemic has unfolded the extent of the academic institutions' readiness to deal with such a crisis. Design/methodology/approach In this vein, the study aimed to identify the perception of translation instructors in teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…It also found that students face issues like adapting to the online environment, a lack of contact and motivation, and a lack of internet connections. [13]. Further, the success of the online form of teaching and learning has a substantial and positive interrelationship with technological assistance, infrastructure availability, faculty and students' perceptions [14].…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…It also found that students face issues like adapting to the online environment, a lack of contact and motivation, and a lack of internet connections. [13]. Further, the success of the online form of teaching and learning has a substantial and positive interrelationship with technological assistance, infrastructure availability, faculty and students' perceptions [14].…”
Section: Review Of Literaturementioning
confidence: 99%
“…The reason for the dissatisfaction of the students may be the unanticipated and sudden conversion of online teaching mode from face to face teaching mode. [7]…”
Section: Satisfaction Of Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…After the outbreak of COVID-19, all levels of schooling in Jordan, primary, secondary and tertiary, have responded to the call by joining the international community’s efforts to adapt to the new situation of COVID-19 (Al-Salman and Haider, 2021; Almahasees et al , 2021). The higher education system of public and private universities took the lead in that endeavor by constructing e-learning platforms and learning management systems supported by the technical infrastructure needed.…”
Section: Introductionmentioning
confidence: 99%
“… Almahasees and Qassem (2021) argue that when it comes to translation studies in particular, the need to understand the material on a practical level requires a far greater degree of direct contact with instructors. They assert that “It is a de facto that teaching translation courses involve face to face communications, and the switch to online mode makes it necessary to scrutinize the faculty’ readiness to teach online and their perceptions of teaching translation courses regarding limitations, challenges, teaching, and assessment strategies” ( Almahasees and Qassem, 2021 , p. 2). They also argue that student-centered rather than teacher-centered instruction methods benefit from recent technological innovations.…”
Section: Introductionmentioning
confidence: 99%